Kurikulum Ekonomi Yang Ideal Bagaimana Implementasinya Pada Siswa Dalam Menyiapkan Kompetensi Abad Ke 21 - Majdi, Muhammad Zainul; Lasmawan, I Wayan; Suharta, I Gusti Putu (Universitas Hamzanwadi, 2023)
This research aims to describe the ideal Economics Curriculum and how it is implemented for students in preparing 21st century competencies. This research method is to use library research which will be analyzed and concluded. Research data was obtained from recordings from books and journals. Data procurement steps include: a global perspective in implementing the ideal economics curriculum and 21st century competencies for students. The conclusion of this research is that an economics curriculum with a global perspective is a curriculum that also contains global insights, not just national or local. The curriculum must be able to bring students to think globally in the sense that students are able to express as much information as possible and this information can be used as a display that directs them to become productive citizens. The competencies needed in the 21st century include: 1) learning innovation skills, 2) information, median and technology skills, 3) life and career skills.